A copper-containing medical titanium alloy and preparation method thereof
By adding Zr elements to medical titanium alloys to form the Zr2Cu precipitation phase, the existing medical titanium alloys have solved the problem of insufficient release of toxic elements and mechanical properties in the human body, and high strength, high toughness and good biocompatibility are achieved.
Patent Information
- Application Number
- CN202411259065.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-09-10
AI Technical Summary
After the existing medical titanium alloy is implanted into the human body, the release of toxic metal ions due to body fluid erosion may cause serious human health diseases. At the same time, the addition of Cu as an antibacterial agent has an adverse effect on the mechanical properties of the titanium alloy.
By adding Zr elements to the Ti-Cu-based alloy, the Zr2Cu precipitation phase is formed, which significantly reduces the alloy β transition temperature, makes Zr2Cu evenly distributed in the alloy, and the α-slats are refined to improve deformation resistance.
It significantly improves the tensile strength and elongation of medical titanium alloys, while maintaining good mechanical properties and biocompatibility, avoiding the release of toxic elements.
Smart Images

Figure CN118773478B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal alloys, and in particular relates to a copper-containing medical titanium alloy and a preparation method thereof. Background Art
[0002] Titanium and titanium alloys have the characteristics of high specific strength, low elastic modulus, strong corrosion resistance and good biocompatibility, and are widely used in the biomedical field, such as artificial hip and knee joints, heart valves, vascular stents, mandibles, skulls, sternums, spines, dental implants, orthodontic fixtures, titanium bone nails, titanium bone plates, etc., becoming one of the most promising medical metal materials after stainless steel and cobalt-chromium alloys.
[0003] TC4 alloy, as a typical α+β duplex alloy, is currently the most widely used medical titanium alloy. Compared with other types of titanium alloys, TC4 alloy has excellent mechanical properties (such as high strength, high hardness and excellent low-cycle fatigue resistance), as well as excellent corrosion resistance and good cost-effectiveness. However, after being implanted in the human body, it is eroded by body fluids for a long time, and toxic metal ions (such as Al and V) are continuously released and accumulated, which may cause serious human health diseases such as peripheral neuropathy, osteomalacia, and Alzheimer's disease. In order to reduce the harm of TC4 alloy to human health to a greater extent, toxic elements such as Al and V must be eliminated.
[0004] Copper-containing titanium alloys have excellent antibacterial properties, good biocompatibility and multifunctionality, and play an important role in the medical field, especially in the field of implants such as orthopedics and dentistry. Copper (Cu) has long been considered an essential trace element for the human body, with many excellent biological properties such as anti-inflammatory, antibacterial, anti-proliferative, good cell compatibility, and stimulation of osteogenesis.
[0005] The invention patent application with publication number CN114457258A discloses an ion-slow-release high-strength Ti-Cu alloy and its 3D printing method and application; the mass percentage of Cu in the alloy is less than or equal to 6%, and the yield strength of the alloy is greater than or equal to 820MPa, the ultimate tensile strength is greater than 900MPa, and the elongation is greater than or equal to 10%; the alloy does not contain β columnar crystals and has no obvious anisotropy, and the macro texture index of the alloy is less than 1.5×random; the alloy has a 35-day Cu 2+ The ion release is less than 0.25 mg / L; the alloy is prepared by laser additive manufacturing technology, and the energy density during laser additive manufacturing is 80-100 J / mm 3 The product designed and prepared by the present invention can be used as a human bone implant material. The present invention has reasonable component design, simple and controllable preparation process, and controllable shape of the formed product, and is suitable for large-scale application of bone transplants with special structures.
[0006] The invention patent application with publication number CN108103353A discloses a medical TiMoCu alloy and a preparation method thereof, belonging to the field of medical titanium alloys and preparation methods thereof; the medical TiMoCu alloy is composed of Ti, Mo and Cu elements; the mass ratio of Ti:Mo:Cu=(100-xy):x:y, x=10-20, y=5-20; its density is 98.5-99.9%; the preparation method is as follows: 1) commercial Ti powder, commercial Mo powder and commercial Cu powder are mixed according to the ratio The invention discloses a method for preparing a medical TiMoCu alloy by mixing the mixture of Ti powder, Mo powder and Cu powder uniformly; 2) pressing the mixture of Ti powder, Mo powder and Cu powder into a blank of a set shape; 3) placing the blank in a mold, heating it to 1150-1200°C at a rate of ≤10°C / min under vacuum, and keeping it warm for 4-6 hours; then continuously pressurizing it at 5-30MPa for 2-4 hours, and cooling it to room temperature with the furnace to obtain a medical TiMoCu alloy; the medical TiMoCu alloy prepared by this patent is used for tooth root or bone replacement, and has a sustained inhibitory effect on Legionella and Staphylococcus aureus.
[0007] However, the addition of Cu as an antibacterial agent disclosed in the above patent has a great adverse effect on the mechanical properties of titanium alloy, which will lead to poor processability and application performance of the alloy. Summary of the invention
[0008] The invention provides a high-strength and high-toughness copper-containing medical titanium alloy.
[0009] The present invention provides a copper-containing medical titanium alloy, wherein the chemical formula of the copper-containing medical titanium alloy is Ti-5Cu-xZr, wherein 0 <x≤45;
[0010] The structure of the copper-containing medical titanium alloy includes primary α laths and Zr2Cu precipitation phases uniformly distributed in the titanium alloy.
[0011] The invention forms a Zr2Cu precipitation phase with the Cu element by adding the Zr element, significantly reduces the alloy β transformation temperature, makes the Zr2Cu uniformly distributed in the alloy, and significantly refines the alloy α lath. The Zr2Cu precipitation phase and the refined structure can effectively hinder the dislocation movement and improve the deformation resistance of the alloy.
[0012] In titanium alloys, Cu, as a eutectoid element, can react with Ti to produce Ti2Cu precipitation phase. The main function of Ti2Cu precipitation phase in titanium alloy is to improve the mechanical properties of alloys through mechanisms such as dispersion strengthening and grain refinement. However, the maximum solubility of Cu in the α phase of titanium alloy is 1.6 at.%, and the maximum solubility in the β phase is 13.5 at.%. In Ti-Cu alloys, since about 5% of Cu elements cannot reduce the β transformation temperature of titanium alloy to a lower value, during the cooling process of the alloy, the β phase first precipitates the primary α phase, and the Cu element is enriched in the remaining β phase. Therefore, the Ti2Cu precipitation phase will only appear in the secondary α phase, which limits the dispersion distribution of the Ti2Cu precipitation phase, and it is often distributed in the alloy structure in the form of aggregation.
[0013] The addition of Zr element makes up for this defect. Zr is considered to be a neutral element, and it also shows a transition from low-temperature hcp α phase to high-temperature bcc β phase in the solid state. Ti and Zr are completely miscible in all phases. The large addition of Zr element can significantly reduce the β transition temperature of titanium alloy. At the same time, Cu element and Zr element can also undergo eutectoid reaction to form Zr2Cu precipitation phase. In their respective binary alloy systems, the eutectoid transformation temperature of Ti and Cu is 790 ℃, and the eutectoid transformation temperature of Zr and Cu is 810 ℃. Zr2Cu is formed before Ti2Cu, consuming Cu element in advance. Therefore, after Zr element is added to copper-containing titanium alloy, the precipitation phase changes to Zr2Cu.
[0014] After adding Zr, during the cooling process of titanium alloy, due to the low enough β transformation temperature, Cu can exist in the β phase in a solid solution state, because the solubility of Cu in the β phase is about 8 times that in the α phase. When the α phase begins to nucleate and grow, the Zr and Cu eutectoid reaction occurs, and the α phase and Zr2Cu precipitation phase are formed almost at the same time, and finally a dispersed Zr2Cu phase is obtained. In addition, Zr can also significantly reduce the size of the α lath of titanium alloy, thereby achieving the dual purpose of dispersion strengthening and fine grain strengthening.
[0015] Preferably, the density of Zr2Cu in the copper-containing medical titanium alloy is 10-130 pieces / (100 μm 2 When the content of Zr2Cu precipitate phase is low, the strengthening effect is not obvious. When the content is too high, the precipitate phase tends to aggregate, causing the alloy to become brittle.
[0016] Preferably, the average width of the primary α-laths is 0.4-3.2 μm.
[0017] Preferably, the copper-containing medical titanium alloy has a tensile strength of 740-1130 MPa and an elongation of 8-16%.
[0018] Preferably, when the mass percentage of Zr is 25-35%, the average width of the primary α lath is 0.5-0.9 μm, and the density of Zr2Cu in the copper-containing medical titanium alloy is 47-109 pieces / (100 μm 2 ).
[0019] The present invention controls the amount of Zr added to obtain primary α laths of appropriate width and Zr2Cu phases of appropriate density, significantly improves the tensile strength while maintaining a good elongation, that is, obtains a copper-containing medical titanium alloy with a tensile strength of 1020-1030 MPa and an elongation of 13-14%. If too much Zr is added, the average width of the primary α laths is too low, and although the tensile strength is further improved, the elongation decreases significantly, which is not conducive to obtaining good comprehensive mechanical properties.
[0020] On the other hand, the present invention also provides a method for preparing the copper-containing medical titanium alloy, comprising:
[0021] (1) preparing a mixed material according to the chemical formula of the copper-containing medical titanium alloy;
[0022] (2) subjecting the mixed material to secondary vacuum consumable smelting to obtain a secondary titanium alloy ingot;
[0023] (3) uniformly annealing the titanium alloy secondary ingot at a temperature exceeding the β transformation point by 40-60 °C for 30-60 min, and then hot rolling with a deformation amount of 75-85%;
[0024] (4) The hot-rolled billet is solution treated to obtain a copper-containing medical titanium alloy.
[0025] Homogenization and hot rolling at 40-60 °C above the β transformation point temperature can fully dissolve the precipitate phase in the high-temperature β phase, ensuring uniform diffusion of each element, while refining the structure, making the alloy α lath width more uniform and the precipitate phase distribution more uniform.
[0026] Preferably, the raw materials for batching are titanium sponge, zirconium sponge and copper particles.
[0027] Preferably, the secondary vacuum consumable melting includes a first vacuum consumable melting and a second vacuum consumable melting;
[0028] The process parameters of the first vacuum consumable melting are: current 0.9-1.8 KA, voltage 30-33 V, pre-vacuum degree 0-1 Pa, working vacuum degree 0-8 Pa;
[0029] The process parameters of the second vacuum consumable melting are: current 0.9-3.6 KA, voltage 31.5-34 V, pre-vacuum degree 0-0.8 Pa, and working vacuum degree 0-5 Pa.
[0030] In the vacuum consumable melting process, melting current and melting voltage are key parameters that need to be carefully controlled. Selecting appropriate melting current and voltage can effectively control the melting rate of metal elements, molten pool temperature and arc length, thereby ensuring uniform dissolution of titanium, zirconium and copper elements and obtaining excellent mechanical properties and chemical stability.
[0031] Preferably, the temperature of the solution treatment is 40-60° C. below the β-transformation point temperature, and the time is 60-90 min.
[0032] More preferably, the temperature of the solution treatment is 630-750°C.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention adds Zr element to Ti-Cu based alloy to form Zr2Cu precipitation phase with Cu element, significantly reduces the alloy β transformation temperature, makes Zr2Cu precipitation phase evenly dispersed in the alloy, and significantly refines the alloy α lath. Without introducing toxic elements, the mechanical properties of medical titanium alloy materials can be greatly improved, and good plastic properties can be maintained. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The DSC test results of the high-strength and high-toughness copper-containing medical titanium alloys obtained in Examples 1-4 of the present invention and Comparative Example 1;
[0036] Figure 2 The XRD patterns of the high-strength and high-toughness copper-containing medical titanium alloys obtained in Examples 1-4 of the present invention and Comparative Example 1;
[0037] Figure 3 The scanning electron micrographs of the high-strength and high-toughness copper-containing medical titanium alloys obtained in Examples 1-4 of the present invention and Comparative Example 1 are shown;
[0038] Figure 4 It is a statistical diagram of the α-slat size of the high-strength and high-toughness copper-containing medical titanium alloy obtained in Examples 1-4 of the present invention and Comparative Example 1;
[0039] Figure 5 This is a comparison chart of the mechanical properties of the high-strength and high-toughness copper-containing medical titanium alloys obtained in Examples 1-4 of the present invention and Comparative Example 1;
[0040] Figure 6 This is a comparison chart of the hardness of the high-strength and high-toughness copper-containing medical titanium alloy obtained in Examples 1-4 of the present invention and Comparative Example 1;
[0041] Figure 7 It is a statistical diagram of the Zr2Cu density of the high-strength and high-toughness copper-containing medical titanium alloy obtained in Examples 1-4 of the present invention and Comparative Example 1;
[0042] Figure 8 The scanning transmission electron image and alloy element distribution result diagram of the high-strength and high-toughness copper-containing medical titanium alloy obtained in Example 3 of the present invention;
[0043] Fig. 9 This is the selected area electron diffraction image of the α phase and Zr2Cu phase of the high-strength and high-toughness copper-containing medical titanium alloy obtained in Example 3 of the present invention. DETAILED DESCRIPTION
[0044] The following will provide a clear and complete description of the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0045] Example 1: Vacuum consumable arc melting Ti-15Zr-5Cu, the specific steps are as follows:
[0046] (1) Weighing materials: Weigh titanium sponge, zirconium sponge and copper particles and mix them in a mass ratio of 80% Ti, 15% Zr and 5% Cu;
[0047] (2) Pressing the electrode: Press the raw materials mixed in proportion into electrode blocks. Each electrode block weighs 1 kg and the raw materials are evenly mixed.
[0048] (3) Welding electrodes: Weld two pressed electrodes into a smelting electrode;
[0049] (4) Vacuum consumable melting of primary ingot: Place the welded melting electrode in a vacuum consumable arc melting furnace for melting, with a current of 1.8 KA, a voltage of 33 V, a pre-vacuum degree ≤ 1 Pa, a working vacuum degree ≤ 8 Pa, and a copper crucible with a diameter of 100 mm to melt a titanium alloy primary ingot with a diameter of 100 mm;
[0050] (5) Vacuum consumable arc melting of secondary ingot: the obtained primary ingot is headed and tailed, and secondary melting is carried out in a vacuum consumable arc melting furnace with a current of 3.6 KA, a voltage of 34 V, a pre-vacuum degree ≤ 0.8 Pa, a working vacuum degree ≤ 5 Pa, and a copper crucible with a diameter of 140 mm is used to melt an ingot with a diameter of 140 mm;
[0051] (6) The ingot was homogenized at 850 °C for 30 min and then hot rolled with 85% deformation.
[0052] (7) The hot-rolled sample was heat treated at 750 °C for 1 h, and finally a high-strength and high-toughness copper-containing titanium alloy, namely TZC-15Zr, was obtained.
[0053] Example 2: Vacuum consumable arc melting Ti-25Zr-5Cu, the specific steps are as follows:
[0054] (1) Weighing materials: Weigh titanium sponge, zirconium sponge and copper particles and mix them in a mass ratio of 70% Ti, 25% Zr and 5% Cu;
[0055] (2) Pressing the electrode: Press the raw materials mixed in proportion into electrode blocks. Each electrode block weighs 1 kg and the raw materials are evenly mixed.
[0056] (3) Welding electrodes: Weld two pressed electrodes into a melting electrode;
[0057] (4) Vacuum consumable melting of primary ingot: Place the welded melting electrode in a vacuum consumable arc melting furnace for melting, with a current of 1.8 KA, a voltage of 33 V, a pre-vacuum degree ≤ 1 Pa, a working vacuum degree ≤ 8 Pa, and a copper crucible with a diameter of 100 mm to melt a titanium alloy primary ingot with a diameter of 100 mm;
[0058] (5) Vacuum consumable arc melting of secondary ingot: the obtained primary ingot is headed and tailed, and secondary melting is carried out in a vacuum consumable arc melting furnace with a current of 3.6 KA, a voltage of 34 V, a pre-vacuum degree ≤ 0.8 Pa, a working vacuum degree ≤ 5 Pa, and a copper crucible with a diameter of 140 mm is used to melt an ingot with a diameter of 140 mm;
[0059] (6) The ingot was homogenized at 810 °C for 30 min and then hot rolled with 85% deformation;
[0060] (7) The hot-rolled sample was heat treated at 710 °C for 1 h, and finally a high-strength and high-toughness copper-containing titanium alloy, namely TZC-25Zr, was obtained.
[0061] Example 3: Vacuum consumable arc melting Ti-35Zr-5Cu, the specific steps are as follows:
[0062] (1) Weighing materials: Weigh titanium sponge, zirconium sponge and copper particles and mix them in a mass ratio of Ti 60%, Zr 35% and Cu 5%;
[0063] (2) Pressing the electrode: Press the raw materials mixed in proportion into electrode blocks. Each electrode block weighs 1 kg, and the raw materials are evenly mixed.
[0064] (3) Welding electrodes: Weld two pressed electrodes into a melting electrode;
[0065] (4) Vacuum consumable arc melting of primary ingot: The welded melting electrode is placed in a vacuum consumable arc melting furnace for melting, with a current of 1.8 KA, a voltage of 33 V, a pre-vacuum degree ≤ 1 Pa, a working vacuum degree ≤ 8 Pa, and a copper crucible with a diameter of 100 mm to melt a titanium alloy primary ingot with a diameter of 100 mm;
[0066] (5) Vacuum consumable arc melting of secondary ingot: the obtained primary ingot is headed and tailed, and secondary melting is carried out in a vacuum consumable arc melting furnace with a current of 3.6 KA, a voltage of 34 V, a pre-vacuum degree ≤ 0.8 Pa, a working vacuum degree ≤ 5 Pa, and a copper crucible with a diameter of 140 mm is used to melt an ingot with a diameter of 140 mm;
[0067] (6) The ingot was homogenized at 760 °C for 30 min and then hot rolled with 85% deformation;
[0068] (7) The hot-rolled sample was subjected to heat treatment at 660 °C for 1 h, and finally a high-strength and high-toughness copper-containing titanium alloy, namely TZC-35Zr, was obtained.
[0069] Example 4: Vacuum consumable arc melting Ti-45Zr-5Cu, the specific steps are as follows:
[0070] (1) Weighing materials: Weigh titanium sponge, zirconium sponge and copper particles and mix them in a mass ratio of 50% Ti, 45% Zr and 5% Cu;
[0071] (2) Pressing the electrode: Press the raw materials mixed in proportion into electrode blocks. Each electrode block weighs 1 kg and the raw materials are evenly mixed.
[0072] (3) Welding electrodes: Weld two pressed electrodes into a smelting electrode;
[0073] (4) Vacuum consumable melting of primary ingot: Place the welded melting electrode in a vacuum consumable arc melting furnace for melting, with a current of 1.8 KA, a voltage of 33 V, a pre-vacuum degree ≤ 1 Pa, a working vacuum degree ≤ 8 Pa, and a copper crucible with a diameter of 100 mm to melt a titanium alloy primary ingot with a diameter of 100 mm;
[0074] (5) Vacuum consumable arc melting of secondary ingot: the obtained primary ingot is headed and tailed, and secondary melting is carried out in a vacuum consumable arc melting furnace with a current of 3.6 KA, a voltage of 34 V, a pre-vacuum degree ≤ 0.8 Pa, a working vacuum degree ≤ 5 Pa, and a copper crucible with a diameter of 140 mm is used to melt an ingot with a diameter of 140 mm;
[0075] (6) The ingot was homogenized at 730 °C for 30 min and then hot rolled with 85% deformation;
[0076] (7) The hot-rolled sample was heat treated at 630 °C for 1 h, and finally a high-strength and high-toughness copper-containing titanium alloy, namely TZC-45Zr, was obtained.
[0077] Comparative Example 1: Vacuum consumable arc melting Ti-5Cu, the specific steps are as follows:
[0078] (1) Weighing materials: Weigh titanium sponge, zirconium sponge and copper particles and mix them in a mass ratio of Ti 95% and Cu 5%;
[0079] (2) Pressing the electrode: Press the raw materials mixed in proportion into electrode blocks. Each electrode block weighs 1 kg and the raw materials are evenly mixed.
[0080] (3) Welding electrodes: Weld two pressed electrodes into a smelting electrode;
[0081] (4) Vacuum consumable melting of primary ingot: Place the welded melting electrode in a vacuum consumable arc melting furnace for melting, with a current of 1.8 KA, a voltage of 33 V, a pre-vacuum degree ≤ 1 Pa, a working vacuum degree ≤ 8 Pa, and a copper crucible with a diameter of 100 mm to melt a titanium alloy primary ingot with a diameter of 100 mm;
[0082] (5) Vacuum consumable arc melting of secondary ingot: the obtained primary ingot is headed and tailed, and secondary melting is carried out in a vacuum consumable arc melting furnace with a current of 3.6 KA, a voltage of 34 V, a pre-vacuum degree ≤ 0.8 Pa, a working vacuum degree ≤ 5 Pa, and a copper crucible with a diameter of 140 mm is used to melt an ingot with a diameter of 140 mm;
[0083] (6) The ingot was homogenized at 920 °C for 30 min and then hot rolled with 85% deformation;
[0084] (7) The hot-rolled sample was heat treated at 820 °C for 1 h, and finally a high-strength and high-toughness copper-containing titanium alloy, namely TZC-0Zr, was obtained.
[0085] like Figure 1As shown in the figure, it can be seen that the β transformation point temperature of TZC alloy decreases with the increase of Zr content, which are 870℃, 800℃, 760℃, 710℃, and 680℃ respectively. At the same time, with the increase of Zr content, the absorption peak of Ti2Cu / Zr2Cu transformed into β phase gradually overlaps with the α transformation peak, which means that after the addition of Zr, during the cooling process of titanium alloy, the β transformation temperature is low enough, and the Cu element exists in the β phase in a solid solution state, and the solubility of Cu element in β phase is about 8 times that in α phase. When α phase begins to nucleate and grow, Zr and Cu eutectic reaction occurs, and α phase and Zr2Cu precipitation phase are formed almost at the same time, and finally a dispersed Zr2Cu phase is obtained.
[0086] like Figure 2 As shown, there are α phase and Ti2Cu phase in Comparative Example 1. With the increase of Zr element content, Zr2Cu phase gradually appears in the alloy, and the peak intensity increases accordingly. In Examples 2-4, the Ti2Cu phase has completely disappeared, which indicates that the Zr2Cu phase plays a major strengthening role in the TZC alloy.
[0087] See also Figure 3 and Figure 4 , Figure 3 The tissue morphology diagrams of Examples 1-4 and Comparative Example 1 are shown, wherein: Figure 3 (a), (b), (c), (d), and (e) represent the organizational morphologies of Comparative Example 1 and Examples 1-4, respectively. Figure 4 The α-slat size statistics of Comparative Example 1 and Examples 1-4 are shown. Figure 4 (a), (b), (c), (d), and (e) represent the grain size statistics of Comparative Example 1 and Examples 1-4, respectively. The TZC-0Zr alloy is mainly composed of α phase and Ti2Cu, and the β phase is completely transformed into α phase and Ti2Cu in this system, and the Ti2Cu precipitated phases are all in an aggregated state. By adding an appropriate amount of Zr element, the microstructure of the titanium alloy becomes a lamellar or basket structure, forming a Zr2Cu precipitated phase with the Cu element, and is evenly dispersed in the alloy, significantly improving the strength of the alloy. In addition, the addition of the Zr element significantly refines the α lath and forms a high-density phase interface with the precipitated phase Zr2Cu. This high-density phase interface can effectively hinder dislocation movement, thereby improving the deformation resistance of the alloy.
[0088] See also Figure 5 , Figure 5The stress-strain curves of Comparative Example 1 and Examples 1-4 are shown. When the mass percentage of the Zr element is 0-15%, the average α lath width of the titanium alloy is about 1.3-3.2 μm, the tensile strength is 740-860 MPa, and the elongation is 15-16%. As the mass percentage of the Zr element increases, the microstructure and mechanical properties of the alloy continue to change. When the mass percentage of the Zr element is 15-25%, the average α lath width of the titanium alloy is reduced to 0.9-1.3 μm, the tensile strength is increased to 860-1020 MPa, and the elongation is 13-15%. When the mass percentage of the Zr element is 25-35%, the average α lath width is further reduced to 0.5-0.9 μm, the tensile strength is increased to 1020-1030 MPa, and the elongation is 13-14%. When the mass proportion of Zr reaches 35-45%, the average α lath width of titanium alloy is further reduced to 0.4-0.5 μm. Although the tensile strength remains between 1030-1130 MPa, the elongation drops significantly to 8-14%. This change pattern reveals that by adjusting the amount of Zr doping, the balance between strength and plasticity of titanium alloy can be achieved to meet the needs of different application scenarios.
[0089] like Figure 6 The microhardness of comparative example 1 and examples 1 to 4 is shown. With the addition of Zr element, the microhardness of the alloy increases. The specific values are: 258.8 HV0.2 / 20, 321.0 HV0.2 / 20, 322.5 HV0.2 / 20, 338.8 HV0.2 / 20, 343.8 HV0.2 / 20.
[0090] Figure 7 The scanning electron micrographs of Comparative Example 1 and Examples 1-4 show the 2 The statistical situation of the number of Zr2Cu phases contained in the number can intuitively reflect the content of Zr2Cu phase in each alloy. The Zr2Cu precipitate phase increases with the increase of Zr element content. When the precipitate phase content is low, the strengthening effect is not obvious. When the content is too high, the precipitate phase will tend to aggregate, causing the alloy to become brittle.
[0091] See also Figure 8 , Fig. 9 , Figure 8 The scanning transmission electron image and alloy element distribution results of Example 3 are shown. Fig. 9 (a) and (b) show the selected area electron diffraction images of Example 3. The alloy element distribution diagram further verifies the existence of the Zr2Cu phase, which has a size of 100-300 nm and is uniformly distributed in the matrix. Fig. 9 (b) is the selected area electron diffraction image corresponding to Zr2Cu, which was identified as C11b structure.
Claims
1. A copper-containing medical titanium alloy, characterized in that: The chemical formula of the copper-containing medical titanium alloy is Ti-5Cu-xZr, wherein 0 <x≤45; The structure of the copper-containing medical titanium alloy includes primary α laths and Zr2Cu precipitated phases uniformly distributed in the titanium alloy; The method for preparing the copper-containing medical titanium alloy comprises: (1) preparing a mixed material according to the chemical formula of the copper-containing medical titanium alloy; (2) subjecting the mixed material to secondary vacuum consumable smelting to obtain a secondary titanium alloy ingot; (3) keeping the titanium alloy secondary ingot at a temperature exceeding the β transformation point by 40-60°C for 30-60 min, and then hot rolling the ingot with a deformation amount of 75-85%; (4) The hot-rolled billet is solution treated to obtain a copper-containing medical titanium alloy.
2. The copper-containing medical titanium alloy according to claim 1, characterized in that: The density of the Zr2Cu precipitated phase in the copper-containing medical titanium alloy is 10-130 / (100 μm 2 ).
3. The copper-containing medical titanium alloy according to claim 1, characterized in that: The average width of the primary α laths is 0.4-3.2 μm.
4. The copper-containing medical titanium alloy according to claim 1, characterized in that: The copper-containing medical titanium alloy has a tensile strength of 740-1130 MPa and an elongation of 8-16%.
5. The copper-containing medical titanium alloy according to claim 1, characterized in that: When the mass percentage of Zr is 25-35%, the average width of the primary α lath is 0.5-0.9 μm, and the density of the Zr2Cu precipitated phase in the copper-containing medical titanium alloy is 47-109 / (100 μm 2 ).
6. The method for preparing a copper-containing medical titanium alloy according to claim 1, characterized in that: The raw materials of step (1) are titanium sponge, zirconium sponge and copper particles.
7. The method for preparing a copper-containing medical titanium alloy according to claim 1, characterized in that: The secondary vacuum consumable melting includes the first vacuum consumable melting and the second vacuum consumable melting; The process parameters of the first vacuum consumable melting are current 0.9-1.8 kA, voltage 30-33 V, pre-vacuum degree 0-1 Pa, and working vacuum degree 0-8 Pa, wherein the pre-vacuum degree and working vacuum degree do not include 0Pa; The process parameters of the second vacuum consumable melting are current 0.9-3.6 kA, voltage 31.5-34 V, pre-vacuum degree 0-0.8 Pa, and working vacuum degree 0-5 Pa, wherein the pre-vacuum degree and working vacuum degree do not include 0 Pa.
8. The method for preparing a copper-containing medical titanium alloy according to claim 1, characterized in that: The temperature of the solution treatment is 40-60° C. below the β transformation point temperature, and the time is 60-90 min.
9. The method for preparing a copper-containing medical titanium alloy according to claim 8, characterized in that: The temperature of the solution treatment is 630-750°C.
Citation Information
Patent Citations
Medical TiMoCu alloy and preparation method thereof
CN108103353A
Ion slow-release high-strength Ti-Cu alloy and 3D printing method and application thereof
CN114457258A
Medical titanium alloy special for implant capable of being immediately implanted and preparation method of medical titanium alloy
CN110157948A